2016
DOI: 10.1038/jhg.2016.110
|View full text |Cite
|
Sign up to set email alerts
|

A partial nuclear genome of the Jomons who lived 3000 years ago in Fukushima, Japan

Abstract: The Jomon period of the Japanese Archipelago, characterized by cord-marked ‘jomon' potteries, has yielded abundant human skeletal remains. However, the genetic origins of the Jomon people and their relationships with modern populations have not been clarified. We determined a total of 115 million base pair nuclear genome sequences from two Jomon individuals (male and female each) from the Sanganji Shell Mound (dated 3000 years before present) with the Jomon-characteristic mitochondrial DNA haplogroup N9b, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
98
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(112 citation statements)
references
References 53 publications
11
98
2
Order By: Relevance
“…We found that IK002 clusters between present-day Southeast and East Asians and the Upper-Paleolithic human remain (40 kya) from Tiányuán Cave [28,33] ( Fig.1A ). Second, when using a smaller number of SNPs (41,264 SNPs) including the present-day Ainu [34] from Hokkaido ( Fig.S1 ), IK002 clusters with the Hokkaido Ainu ( Fig.S4 ), supporting previous findings that they are direct descendants of the Jomon people [14,[34][35][36][37][38][39][40][41] . Thus, the PCA plot showed that IK002 is slightly different from present-day people in East Eurasia and Japan except for the Hokkaido Ainu.…”
Section: Testing Whether Ik002 Is the Direct Descendant Of The Upper supporting
confidence: 79%
See 1 more Smart Citation
“…We found that IK002 clusters between present-day Southeast and East Asians and the Upper-Paleolithic human remain (40 kya) from Tiányuán Cave [28,33] ( Fig.1A ). Second, when using a smaller number of SNPs (41,264 SNPs) including the present-day Ainu [34] from Hokkaido ( Fig.S1 ), IK002 clusters with the Hokkaido Ainu ( Fig.S4 ), supporting previous findings that they are direct descendants of the Jomon people [14,[34][35][36][37][38][39][40][41] . Thus, the PCA plot showed that IK002 is slightly different from present-day people in East Eurasia and Japan except for the Hokkaido Ainu.…”
Section: Testing Whether Ik002 Is the Direct Descendant Of The Upper supporting
confidence: 79%
“…A critical challenge for ancient genome analysis in the Japanese archipelago is the inherent nature of warm and humid climate conditions, and the soils indicating strong acidity because of the volcanic islands, which generally result in poor DNA preservation [12,13] . A partial genome of a 3,000-years old Jomon individual from the east-north part of the main-island (Honshu) Japan was reported, but with very limited coverage (~ 0.03-fold) due to the poor preservation [14] . To identify the origin of the Jomon people, we sequenced a 1.85-fold genomic coverage of a 2,500-years old Jomon individual (IK002) excavated from the central part of the Japanese archipelago [15] .…”
Section: Introductionmentioning
confidence: 99%
“…A new nuclear genomic sequence of a Sanganji Jomon (Tohoku region) specimen indicated that the Jomon people were derived from an ancestral East Eurasian population prior to the currently recognizable population diversification (Kanzawa-Kiriyama et al, 2016), as previously mentioned from an osteological point of view (Yamaguchi, 1992). Determining the geographic origins of the candidate Jomon ancestral populations is still difficult; thus, we should expand the plausible target to more ancient Pleistocene fossils as previously suggested (Yamaguchi, 1992;Mizoguchi, 2011) and attempt to recover more genetic data on relevant ancient populations.…”
Section: Discussionmentioning
confidence: 84%
“…We have therefore proceeded to determine nuclear DNA sequences that are much larger than mtDNA. The results (Kanzawa-Kiriyama et al 2017) clearly indicate that the present-day Japanese have inherited the DNA of Jomon people, as best represented by the Ainu who are direct descendants of the Jomon. This confirms Hanihara's (1991) by ANU Press, The Australian National University, Canberra, Australia.…”
Section: Descendants Of Ancient Human Migrants To the Japanese Archipmentioning
confidence: 79%